2017
DOI: 10.3390/ijms18020424
|View full text |Cite
|
Sign up to set email alerts
|

A Gin4-Like Protein Kinase GIL1 Involvement in Hyphal Growth, Asexual Development, and Pathogenesis in Fusarium graminearum

Abstract: Fusarium graminearum is the main causal agent of Fusarium head blight (FHB) on wheat and barley. In a previous study, a GIN4-like protein kinase gene, GIL1, was found to be important for plant infection and sexual reproduction. In this study we further characterized the functions of GIL1 kinase in different developmental processes. The Δgil1 mutants were reduced in growth, conidiation, and virulence, and formed whitish and compact colonies. Although phialide formation was rarely observed in the mutants, deleti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Wheat ( Triticum aestivum L.) is the third-largest food crop after maize and rice [ 1 ]. F. graminearum (Fg) is one of the common fungal diseases that threatens many economic crops, such as wheat, rice, barley, and maize [ 2 , 3 ]. The fungus causes growth and yield losses in wheat by causing Fusarium seedling blight (FSB) and Fusarium head blight (FHB) [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Wheat ( Triticum aestivum L.) is the third-largest food crop after maize and rice [ 1 ]. F. graminearum (Fg) is one of the common fungal diseases that threatens many economic crops, such as wheat, rice, barley, and maize [ 2 , 3 ]. The fungus causes growth and yield losses in wheat by causing Fusarium seedling blight (FSB) and Fusarium head blight (FHB) [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…In fungi, delayed hyphal growth can be also associated with increased hyphal branches. For example, deletions of the protein kinase gene Gil1 in A. nidulans and the septin gene AspB in F. graminearum lead to increased hyphal branching and abnormal growth (Hernández‐Rodríguez et al., 2012 ; Yu et al., 2017 ). RNA‐Seq analysis showed that the septin genes UV8b_01520 , UV8b_06116 and UV8b_08253 , and the majority of branching‐associated protein kinase genes were significantly downregulated in the Δ Uvhos3 mutant (Table S5 ).…”
Section: Discussionmentioning
confidence: 99%
“…A gene for the serine/threonine-protein kinase GIN4 (MAC_00865) was found to be upregulated. In Fusarium graminearum, the disruption of a GIN4-like protein kinase gene increased the fungal tolerance to cell wall stress [ 27 ], suggesting a possibility that the Gin4 regulation of the fungal tolerance to cell wall stress by MaOpy2 functioned differentially in M. acridum . In addition, ∆ MaOpy2 exhibited a higher susceptibility to the cell-wall-disturbing agent CR, which was consistent with that in C. albicans [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Table S2: Differentially expressed genes. Table S3: DEGs involved in stress tolerance and conidiation pattern shift [ 26 , 27 , 33 , 34 , 35 , 36 ].…”
mentioning
confidence: 99%